2015
DOI: 10.1186/s12888-015-0502-1
|View full text |Cite
|
Sign up to set email alerts
|

Psychotic and schizotypal symptoms in non-psychotic patients with obsessive-compulsive disorder

Abstract: BackgroundResearch is scarce with regard to the role of psychotic and schizotypal symptoms in treatment of obsessive-compulsive disorder (OCD). The aim of the current study was to investigate the occurrence and specificity of psychotic and schizotypal symptoms among non-psychotic OCD patients, and to examine whether such symptoms was associated with response to exposure and response prevention (ERP), and whether ERP for OCD had an impact on psychotic and schizotypal symptoms.MethodsNon-psychotic OCD patients (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…With respect to metacognitions and OCD, one study found that change in metacognitions accompany improvement in OCD symptoms [ 53 ], and treatment that focus on metacognitive mechanisms has led to positive treatment results for OCD [ 55 , 56 ]. Exposure therapy for OCD is also associated with reductions in psychotic and schizotypal symptoms [ 57 ]. With respect to metacognitions and psychosis, a study has indicated that treatment with focus on metacognitions is a feasible for patients with psychosis [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…With respect to metacognitions and OCD, one study found that change in metacognitions accompany improvement in OCD symptoms [ 53 ], and treatment that focus on metacognitive mechanisms has led to positive treatment results for OCD [ 55 , 56 ]. Exposure therapy for OCD is also associated with reductions in psychotic and schizotypal symptoms [ 57 ]. With respect to metacognitions and psychosis, a study has indicated that treatment with focus on metacognitions is a feasible for patients with psychosis [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…10,31,32 Furthermore, these patients commonly exhibit major depression, posttraumatic stress disorder, substance use, 32,33 depression and bipolar disorder 34 as comorbid conditions, as well as increased severity of OCD and greater general psychopathology in comparison to OCD counterparts. [32][33][34] Interestingly, hoarding has been consistently associated with the SPD-OCD group 29,35 and has been reported as a predictor of schizotypal personality traits (SPT) in OCD. 36 Further clinical investigation is needed in order to elucidate the potential connection between hoarding symptoms and SPT, as well as its implication to the schizo-obsessive spectrum disorders.…”
Section: Spd-ocd Associationmentioning
confidence: 99%
“…Schizotypal personality disorder (SPD) associated with OCD displays a more deteriorative course, poorer insight (with some patients exhibiting delusional transformation of obsessions), more negative symptoms, lower functioning, greater cognitive impairment, treatment resistance, and poorer prognosis than “pure” OCD 10 31 , 32 Furthermore, these patients commonly exhibit major depression, posttraumatic stress disorder, substance use, 32 , 33 depression and bipolar disorder 34 as comorbid conditions, as well as increased severity of OCD and greater general psychopathology in comparison to OCD counterparts 32 34 Interestingly, hoarding has been consistently associated with the SPD-OCD group 29 , 35 and has been reported as a predictor of schizotypal personality traits (SPT) in OCD 36 .…”
Section: Clinicsmentioning
confidence: 99%
“…The relationship between OCD and psychosis was first discussed about 80 years ago. According to recent studies, there might be no boundary between obsessive thoughts and delusions, as some patients with OCD may lose their insight, and their obsessive thoughts may turn into delusions (19,20). The strength of obsessive thoughts in patients with OCD, might range from overvalued ideas to delusion.…”
Section: Discussionmentioning
confidence: 99%